A REPRESENTATION OF ZAINICHI AS SUBALTERNS IN MIN JIN LEE’S PACHINKO: POSTCOLONIAL STUDIES - Susilawati, Ayu; Wajiran, Wajiran (Lire Journal (Journal of Linguistics and Literature), 2024)
This study aims to analyse the representation of Zainichi as Subalterns in Min Jin Lee's Pachinko. The subject of the subalterns is the Korean diaspora, who are struggling against oppression, marginalization, and discrimination in Japanese society. The researcher uses descriptive and qualitative research methods, while Gayatri Chakravorty Spivak's subaltern theory has been applied to the selected text. The data will be taken from many aspects such as dialogues, depiction of the situation or event, characters, etc. This study analysed two problems: (1) How is the representation of Zainichi as Subalterns in Min Jin Lee's Pachinko? (2) How is the subaltern resisting the impact of subalternity in Min Jin Lee's Pachinko? First, the results of this study reveal that the form of discrimination and marginalization experienced by Zainichi are indicative of the existence of subalternity in Japan, which was represented in the Pachinko written by Min Jin Lee. Secondly, this research reveals that hybridity and ethical politics became Zainichi's way of speaking out as a form of resistance to subalternity. Moreover, the Korean diaspora and their descendants represented the subalterns in Pachinko. At the same time, women are considered inferior to men and people who have ideologies and beliefs that are different from Japanese ideology. This study is fascinating because subaltern issues exist long after the postcolonial period